level of teaching practices of mathematics teachers according to the skills of the twenty-first century - Saif kareem muslim - Ayat Mohammed Jebur ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
current research aims to know level of teaching practices of mathematics teachers according to skills of the twenty-first century. Researcher followed   descriptive approach to achieve the goal of the research, and the community consisted of mathematics teachers and female teachers in middle schools who numbered (156) teachers and schools, including (30) teachers and schools of the basic research sample randomly selected, the research tool represented by the observation card for the skills of the twenty-first century, which consisted of ( 30) items divided into three domains (learning and creativity skills, digital culture skills, life and profession skills), the validity and reliability of the tool were confirmed to be applied to the research sample after analyzing the statistical data based on (SPSS), and the results showed:1- level of teaching practices of mathematics teachers and female teachers according to the skills of the twenty-first century was weak2- There are differences in the level of teaching practices of mathematics teachers and female teachers according to the skills of the twenty-first century due to the variable (gender) in favor of males.3- There are no differences in the level of teaching practices of mathematics teachers according to the skills of the twenty-first century due to the variable (experience).In light of the results, a set of recommendations and suggestions were presented